Swearing-in Ceremony for Juvenile Court Referee Nancy Cisneros - Watkins, Howard::::::::: (1988)
Front row: Justices Donald Franson, Sr., Wickson Woolpert, Robert Martin, Charles Hamlin, Presiding Justice George Brown, Pauline Davis Hanson (ret.), Hollis Best, and Jay Balentine. Middle row: Hon. Nancy Cisneros, Justice James Ardaiz, Judges James Thaxter, Robert Mardikian, James Quaschnick, Mario Olmos, and James Aaron; Back Row: Judge Thomas Harris, Judge Frank Creede, Jr., ?, Referee Philip Silva, Judges John Fitch, Victor Papadakis, and Nicholas DiBiaso